Clinical Outcomes Following Implantation of Thin-Strut, Bioabsorbable Polymer-Coated, Everolimus-Eluting SYNERGY Stents: Final 5-Year Results of the EVOLVE II Randomized Trial. (September 2019) - Kereiakes, Dean J.; Windecker, Stephan; Jobe, R. Lee; Mehta, Shamir R.; Sarembock, Ian J.; Feldman, Robert L.; Stein, Bernardo; Dubois, Christophe; Grady, Timothy; Saito, Shigeru; Kimura, Takeshi; Underwood, Paul; et al.
Abstract : Background: The thin-strut SYNERGY stent has an abluminal everolimus-eluting bioabsorbable polymer coating designed to facilitate vascular healing and reduce risk of stent thrombosis. In the multicenter, randomized EVOLVE II trial (The EVOLVE II Clinical Trial to Assess the SYNERGY Stent System for the Treatment of Atherosclerotic Lesion[s]), SYNERGY was noninferior to the durable polymer PROMUS Element Plus everolimus-eluting stent for the primary end point of 1-year target lesion failure. Longer-term clinical follow-up will support the relative efficacy and safety of SYNERGY. Methods: Patients with ⩽3 native coronary lesions (reference vessel diameter ≥2.25–⩽4.00 mm; length ⩽34 mm) in ⩽2 major epicardial vessels were randomized 1:1 to SYNERGY (N=838) or PROMUS Element Plus (N=846). EVOLVE II included a Diabetes substudy which pooled patients with diabetes mellitus from the randomized controlled trial (n=263) and from a sequential, single-arm substudy (N=203). Results: The 5-year target lesion failure rate was 14.3% for SYNERGY and 14.2% for PROMUS Element Plus ( P =0.91). Landmark analysis demonstrated similar rates of target lesion failure from discharge to 1-year ( P =0.90) and from 1 to 5 years ( P =0.94). Definite/probable stent thrombosis was infrequent in both arms (SYNERGY 0.7% versus PROMUS Element Plus 0.9%; P =0.75). There were no significant differences in the rates of cardiac death, myocardial infarction, or revascularization. Among patients with diabetes mellitus, the target lesion failure rate to 1-year was noninferior to a prespecified performance goal and to 5 years was 17.0%. Conclusions: SYNERGY demonstrated comparable outcomes to PROMUS Element Plus, with low rates of stent thrombosis and adverse events through 5 years of follow-up. Five-year clinical outcomes were favorable in patients with diabetes mellitus. These data support the long-term safety and effectiveness of SYNERGY in a broad range of patients. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01665053. Abstract : Supplemental Digital Content is available in the text.